Essential oils and their binary combinations have synergistic and antagonistic insecticidal properties against Anopheles gambiae s. l. (Diptera: Culicidae). (July 2022) - Wangrawa, Dimitri W.; Ochomo, Eric; Upshur, Forde; Zanré, Nicolas; Borovsky, Dov; Lahondere, Chloé; Vinauger, Clement; Badolo, Athanase; Sanon, Antoine
Abstract: Botanical biopesticides have potential for use in mosquito control because they exhibit low mammalian toxicity, are readily biodegraded, show target speciﬁcity and insecticidal activity. As populations of mosquito species grow more resistant to currently used organic insecticides, a need for new and effective insecticides for vector control becomes more urgent. This study reports the effects of synergistic and antagonistic essential oils (EOs) from Cymbopogon schoenanthus, Lantana camara, Lippia chevalieri and Lippia multiflora and their binary combinations against Anopheles gambiae s. l. larvae and adults. EOs insecticidal properties were tested with third to fourth-instar larvae and, non-blood-fed 3–5-day old field-collected An . gambiae using WHO and CDC bottle bioassays, respectively. Many compounds were found in the EOs mixtures. All EOs showed larvicidal and adulticidal activities with mortality from 0 to 100% against An. gambiae which were concentration dependent and EOs specific. EO mixture from C. schoenanthus and L. multiflora showed synergistic effect with LC50 of 38 ppm and EOs from L. chevalieri and C. schoenanthus showed antagonistic effect against larvae with LC50 of 100.84 ppm. On the other hand, EOs combinations showed additive effect on all adults. This study describes the potential of using EOs and their synergistic mixtures as potential insecticide(s) as a safer alternative to synthetic insecticides. Highlights: Larvicidal and adulticidal toxicity of essential oils isolated from leaves of Cymbopogon schoenanthus, Lantana camara, Lippia chevalieri and Lippia multiflora against Anopheles gambiae s. l. Synergistic and antagonistic effect of essential oil against An . gambiae larvae. Phytochemical and GC-MS analysis were performed to show the presence of phytocompounds in essential oils and new compounds in their binary combinations. Essential oils are eco-friendly and cost-effective botanicals of larvicidal and adulticidal nature.